Prognosis and prognostic factors in non‐traumatic acute‐onset compressive mononeuropathies – radial and peroneal mononeuropathies. Issue 6 (26th March 2013) - Bsteh, G.; Wanschitz, J. V.; Gruber, H.; Seppi, K.; Löscher, W. N.
<x xml:space="preserve">Abstract</x> Background and purpose Little is known about the natural history of non‐traumatic compressive mononeuropathies. To improve patient management, prognostic factors and outcome in patients with non‐traumatic peroneal and radial mononeuropathies were studied. Methods Retrospective clinical, electrophysiological and sonographic data of patients with non‐traumatic peroneal and radial mononeuropathies were evaluated. Clinical, electrophysiological and sonographic evaluations had to take place 2–12 weeks after symptom onset and follow‐up had to be for >6 months. Results Twenty‐five patients with peroneal mononeuropathy and 58 with radial mononeuropathy were included. Mean follow‐up was 8.9 ± 2.4 months. Approximately 90% of patients recovered to a muscle strength of British Medical Research Council grade 4 or 5. Multiple logistic regression analysis revealed conduction block on nerve conduction studies, younger age and less severe initial weakness as indicators for a good prognosis. Peripheral nerve ultrasound was not prognostic in the 40 patients where it was available. Conclusions The present study shows a good prognosis for spontaneous recovery after non‐traumatic acute‐onset compressive peroneal and radial mononeuropathies. Patients with denervation on needle electromyography, older age and severe initial weakness have a poorer prognosis and should be closely monitored to facilitate timely surgery whenever weakness persists. Peripheral nerve ultrasound seems to be of limited prognostic value in these mononeuropathies.